Ultrafast and Broadband Terahertz Modulator With Polarization Selectivity - Hongchuan He; Qiuping Huang; Honglei Cai; Yi Zhao; Xiaoxia Lin; Hao Cheng; Tian Ma; Jianlin Wang; Haoliang Huang; Ming Yin; Zhengping Fu; Yalin Lu (IEEE Photonics Journal, 2019)
We demonstrate a broadband and polarization selective terahertz modulator with ultrafast modulation speed, based on the Si grating metasurface on the Sapphire substrate. The Si layer is implanted with B+ and subsequently annealed, which significantly reduces the lifetime of carriers and increases the carrier density, and thus realizes ultrafast and efficient modulation. Our modulator achieves modulation depth up to 60% for the x-polarized THz wave and less than 1% for the y-polarized THz wave in the frequency ranging from 0.5 to 2.5 THz, with switch-on and switch-off time of modulation in 20 ps and around 300 ps, respectively. The carrier dynamics of the fabricated Si grating is also studied to illustrate the ultrafast modulated mechanism. Our results pave the way for ultrafast manipulation of terahertz spectrum and shows great potential in terahertz communication.